Wittgenstein on mind and language - Stern, David G. (Oxford Univ. Press, 1995)
Wittgenstein on Mind and Language traces the development of a number of central themes in Wittgenstein's philosophy, including his conception of philosophical method, the picture theory of meaning, the limits of language, the application of language to experience, his treatment of private language, and what he called the "flow of life." It also explains how the unpublished manuscripts and typescripts were put together and why they often provide better evidence of the development of his ideas than can be found in his published writing. Arguing that Wittgenstein's views are often much more simple (and more radical) than we have been led to believe, Wittgenstein on Mind and Language provides an overview of the development of Wittgenstein's thought and brings to light aspects of his philosophy that have been almost universally neglected.
Teilw. zugl.: Berkeley, Calif., Univ., Diss., 1991
Keywords: Wittgenstein, Ludwig <1889-1951> / Contributions in philosophy of language; Wittgenstein, Ludwig <1889-1951> / Contributions in philosophy of mind; Wittgenstein, Ludwig, 1889-1951 -- Contributions in philosophy of mind; Wittgenstein, Ludwig, 1889-1951 -- Contributions in philosophy of language; Wittgenstein, Ludwig -- 1889-1951; Geschichte 1900-2000; Filosofie van de geest; Taalfilosofie; Geschichte; Philosophie; Sprache; Philosophy of mind -- History -- 20th century; Language and languages -- Philosophy -- History -- 20th century; Bewusstsein; Hochschulschrift